Enhanced Bilosomal Properties Resulted in Optimum Pharmacological Effects by Increased Acidification Pathways - Armin Mooranian; Thomas Foster; Corina M. Ionescu; Daniel Walker; Melissa Jones; Susbin Raj Wagle; Bozica Kovacevic; Jacqueline Chester; Edan Johnston; Elaine Wong; Marcus D. Atlas; Momir Mikov; et al. (MDPI AG, 2021)
Introduction: Recent studies in our laboratory have shown that some bile acids, such as chenodeoxycholic acid (CDCA), can exert cellular protective effects when encapsulated with viable β-cells via anti-inflammatory and anti-oxidative stress mechanisms. However, to explore their full potential, formulating such bile acids (that are intrinsically lipophilic) can be challenging, particularly if larger doses are required for optimal pharmacological effects. One promising approach is the development of nano gels. Accordingly, this study aimed to examine biological effects of various concentrations of CDCA using various solubilising nano gel systems on encapsulated β-cells. Methods: Using our established cellular encapsulation system, the Ionic Gelation Vibrational Jet Flow technology, a wide range of CDCA β-cell capsules were produced and examined for morphological, biological, and inflammatory profiles. Results and Conclusion: Capsules' morphology and topographic characteristics remained similar, regardless of CDCA or nano gel concentrations. The best pharmacological, anti-inflammatory, and cellular respiration, metabolism, and energy production effects were observed at high CDCA and nano gel concentrations, suggesting dose-dependent cellular protective and positive effects of CDCA when incorporated with high loading nano gel.